ПРОБЛЕМЫ ОБОЗНАЧЕНИЯ И КЛАССИФИКАЦИИ РЕЛИГИОЗНО МАРКИРОВАННЫХ ФРАЗЕОЛОГИЧЕСКИХ ЕДИНИЦ - Галиева, М.Р. (SCIENCE and SOCIETY, 2018)
The article considers different terminological nominations and approaches to the investigation of religiously marked phraseological units (RMPhU). RMPhU are phraseological units of biblical origin and phraseological units that have religiously marked component. The analysis of theoretical literature has shown that many terms are used to denote this linguistic phenomena. The classifications that are worked out highlights only some aspects of this linguistic phenomenon and mostly devoted to the etymological classification of RMPhU. The article regards this phenomena as RMPh.U and offers several criteria for their analysis.